Difusión y divulgación: la organización de la información científica en CIENCIA ergo-sum - Ramírez Nava, Jorge (CIENCIA ergo-sum; Vol. 24 Núm. 3: CIENCIA ergo-sum (noviembre 2017-febrero 2018), 2017)
Editorial